Linear and logistic regression: A medical perspective - S. Gothai Nachiyar; Kalaivani Annadurai; Rekha Palani (Al Ameen Journal of Medical Sciences, 2025)
Logistic regression as the standard tool for extending the concepts of linear regression to binary outcomes. Binary outcomes have two states, such as death (dead or alive) or allergic reaction (present or absent), in contrast to continuous variables, like blood pressure or glucose levels, which lie on a continuum of possible values. Logistic regression concepts such as odds, odds ratio, logit transformation, logistic curve, assumption, selecting dependent and independent variables, model fitting, reporting and interpreting were presented [1].